2021
DOI: 10.1149/1945-7111/ac208d
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Three-Electrode Cells for Improving Solid State Batteries

Abstract: A three electrode cell for use with solid electrolytes is presented. The cell provides a stable reference voltage and leads artefact-free impedance spectra while being easily assembled and air-tight. To prove its versatility several combinations of electrodes and electrolytes were employed, enabling to rapidly assess the main differences between argyrodite vs. lithium phosphorous sulphide electrolytes, oxide vs. sulphide active materials or Li-In alloy based anode vs. Li foil anode. This new cell design offers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 29 publications
(54 reference statements)
0
13
0
Order By: Relevance
“…The three-electrode cell setup was modified from the two-electrode cell by placing 15 μm Al metal foil as the RE current collector between two polyetherimide body parts, and the cell assembly was realized as explained in our previous work …”
Section: Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The three-electrode cell setup was modified from the two-electrode cell by placing 15 μm Al metal foil as the RE current collector between two polyetherimide body parts, and the cell assembly was realized as explained in our previous work …”
Section: Experimental Sectionmentioning
confidence: 99%
“…The three-electrode cell setup was modified from the two-electrode cell by placing 15 μm Al metal foil as the RE current collector between two polyetherimide body parts, and the cell assembly was realized as explained in our previous work. 33 Galvanostatic cycling studies were carried out in the voltage range of 2.1−3.6 V versus LiIn/In at room temperature at C/20 (C corresponds to 1 mol of Li per mole of the active material in 1 h). Three-electrode full-cell impedance spectra were measured upon galvanostatic cycling at 3.2, 3.4, 3.6, 3.4, 3.2, and 2.1 V after 4 h rest at each point using a 10 mV sinusoidal perturbation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In situ electronic conductivity cells were built using the three‐electrode cell setup, [ 24 ] where an aluminum mesh (thickness of 60 µm) was implemented at the level of the reference connection. The cell integrates 30 to 40 mg of cathode composites for TMLO (depending on the composite density), and 20–25 mg of composite for LTO, which was further pressed at 0.5 t cm − 2 so as to be embedded in between the Al mesh and the working electrode piston.…”
Section: Methodsmentioning
confidence: 99%
“…In order to unequivocally measure the properties of a single electrode, the use of a reference electrode (RE) and the construction of a three-electrode cell are then mandatory. While three-electrode (3E) cells are well established for lithium-ion batteries, there are only a few publications on 3E cells, including EIS measurements for SSBs. A major reason for this is the difficult construction of a proper RE in the solid-state environment. Theoretical analyses of the influence of the RE position relative to the electrodes and the RE geometry on the respective cell impedances were published by Ivers–Tiffée and co-workers. ,, They reported that while a mesh-shaped RE might inhibit ion migration more than a wire-shaped RE, chemical and geometrical asymmetries have a smaller or no influence on the cell impedance. , Additionally, the higher surface area of a mesh, compared to that of a wire, lowers the impedance of the RE, and measurement artifacts caused by the RE may be less problematic. However, as Simon et al and Hertle et al demonstrated with a μ-sized wire-type RE, the proper separation of the two-electrode impedance works very well in SSBs and leads to consistent results. , …”
Section: Introductionmentioning
confidence: 99%